Design and Development of a Prototype for a Pascal’s Law & IoT applied Automatic Hydraulic Braking System - Paneru, Biplov; Paneru, Bishwash (Journal of Electronics and Informatics, 2023)
The widespread adoption of autonomous vehicles continues to increase along with various scientific and technological advancements, and this is necessitating the application of essential accident prevention measures. This research presents the design and development of an innovative hydraulic braking system utilizing readily available components and materials. The Pascal’s law of pressure is very applicable in modern hydraulic braking mechanisms. The system employs an ultrasonic sensor, a repurposed disk, a motor, and a solenoid lock controlled by a relay to create an effective braking mechanism. The primary objective of this research is to demonstrate the feasibility of constructing a functional braking system based on Pascal’s law of pressure, using locally sourced materials, catering to resource-constrained environments. The proposed hydraulic braking system functions as follows: when the ultrasonic sensor detects an object within its proximity (approximately 20 centimeters), it triggers the relay, which activates the solenoid lock. The solenoid lock’s action initiates the movement of a syringe compressor, exerting pressure on the hydraulic fluid. This pressure is then transmitted to the repurposed DVD (Digital Versatile Disk), which serves as the braking element. As the disk is pressed against a surface, the resulting friction decelerates the system, effectively applying the brake. Finally, data is evaluated in the IoT (Internet of Things) platform ThingSpeak to identify safe and harmful states.